Effect of Water Magnetic Treatment on Changes in Total Soluble Proteins and some Enzyme Activities in the Intestine of Common Carp Cyprinus Carpio: A.A. Thaker1 , A.F.Shenear2 and F. jassim1 - Thaker, A. A. (The Iraqi Journal of Veterinary Medicine, 2012)
The aim of this study is to follow the changes in proteins and some enzyme activities inCyprinus carpio were exposed Fish intestine of common carp exposed to magnetized water.to magnetized water for 8 days. Magnetic intensities of 750, 1500 and 3000 gauss were usedto magnetize water. The activities of enzymes (alkaline phosphatase, acid phosphatase, ALTand AST) were followed in the fish intestine. Besides, an electrophoresis change in esteraseenzyme was used to fallow. Activities of all enzymes were increased in the intestine of fishexposed to magnetized water. A new bands of esterase were induced which stained with alphanaphthyl acetate on polyacrylamid gel electrophoresis, while no changes in protein bandswere observed.